Interactive effects of road salt and sediment disturbance on the productivity of seven common aquatic macrophytes. (16th April 2018) - Stoler, Aaron; Sudol, Kelsey; Mruzek, Joseph; Relyea, Rick
Abstract: Around the world, freshwater ecosystems are subjected to numerous stressors that can alter community composition in favour of stress‐tolerant species. Because combinations of stressors often result in non‐additive interactions, elucidating responses to isolated and combined stressors is important to understand the ecological responses to anthropogenic disturbance. In this study, we explored the responses of common macrophyte species to two stressors of increasing concern: elevated salinity from road salt applications and turbidity from human recreational activities and shoreline development. The independent and interactive effects of environmentally relevant salt concentrations and turbidity on macrophyte productivity have received little attention. We hypothesised that both stressors in isolation would reduce macrophyte productivity and that the two stressors combined will lead to a greater (i.e. synergistic) reduction in productivity. To test these hypotheses, we conducted dark‐ and light‐bottle experiments on seven species of native and invasive macrophytes under a factorial combination of three salt concentrations (0, 500 and 3, 000 added mg Cl − L −1 ) and two turbidity conditions (clear and turbid via a disturbance to the sediment). On average, macrophytes exhibited reduced productivity in response to increased salt, but results were highly species‐specific. Several species exhibited a unimodal response to elevated salinity, whereas Elodea canadensis exhibited a positive response to the high‐salt treatment. Similarly, macrophytes exhibited an average reduction in productivity under turbid conditions, but analysis of species‐specific responses revealed both neutral and negative responses. Combining the two stresses yielded non‐additive responses for some species. Specifically, Myriophyllum spicatum appeared to suffer from the combination of salt and turbidity, whereas Elodea canadensis and Ceratophyllum demersum benefited from the combination. Our results suggest that increased anthropogenic disturbance of freshwater ecosystems can dramatically alter macrophyte species metabolism and might stimulate the growth of some species while deterring the growth of others.